2012
DOI: 10.1021/jp3085815
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Hydrophobic Polyelectrolyte Solution in Mixed Aqueous/Organic Solvents Revealed by Neutron Scattering and Viscosimetry

Abstract: We investigate in this paper the influence of the improvement of the solvent quality on the structure and the viscous properties of solutions of an hydrophobic polyelectrolyte, poly(styrene-co-sodium styrenesulfonate): PSS. The solvent used is a mixture of water and an organic solvent, THF, which is also slightly polar. We use small angle neutron scattering in the semidilute regime and viscosimetry as a function of concentration in dilute and semidilute unentangled regime. The structure, namely the scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 57 publications
4
35
0
Order By: Relevance
“…In general, electrostatic repulsion interaction between segments can be screened all or in part by counterions around chains, which is also considered as one of key factors to influence chains conformation . According to the research by Essafi et al, the degree of intermolecular aggregation is higher for stronger charged hydrophobic polyelectrolytes . It suggested that more counterions are distributed around a chain in the case of hydrophobic polyelectrolytes with high f i .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, electrostatic repulsion interaction between segments can be screened all or in part by counterions around chains, which is also considered as one of key factors to influence chains conformation . According to the research by Essafi et al, the degree of intermolecular aggregation is higher for stronger charged hydrophobic polyelectrolytes . It suggested that more counterions are distributed around a chain in the case of hydrophobic polyelectrolytes with high f i .…”
Section: Resultsmentioning
confidence: 99%
“…From the viewpoints of interactions, numerous studies showed that the solvent plays an important role by controlling monomers–solvent and monomers–monomers interaction . On the one hand, when the solvent qualify is low, hydrophobic attractive interaction is high, causing the collapse . On the other hand, few researches proposed that when the dielectric permittivity of the solvent is low, the effect of condensation of counterions onto chains is obvious, causing the decrease of electrostatic repulsive interaction between segments and the collapse of molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can also note that THF addition causes a conformation transition from a collapsed conformation to a stretched one for PSSNa f = 0.37, however for the fully charged PSSNa f = 1, THF addition is not accompanied by transition conformation 37 and this difference may also affect the release of the dye from the two polyelectrolytes, being faster for PSSNa f = 0.37.…”
Section: Effect Of Added Tetrahydrofuran "Thf"mentioning
confidence: 97%
“…At higher concentrations but still below the overlap concentration, c*, a transition regime of semiflexible polyions was identified. In this regime, beside a fast diffusion, that was found to follow a power law, [38][39][40][41] a slow mode was observed in many systems even if its origin is still under debate. According to the most accredited proposals, this slow mode is related with the presence of multichain domains [36,37,42,43] whose formation is highly influenced by many factors (such as polyelectrolyte molecular weight [36,37,44] and concentration [37,44]); notwithstanding some controversies, the slow diffusion coefficient was found to decrease with concentration [36,37,44].…”
Section: Dlsmentioning
confidence: 99%